Concrete Asphalt Marshall Stability Using Concrete Objective Waste - Sumargono Sumargono; Agata Iwan Candra; Ahmad Ridwan; Budi Winarno; Ki Catur Budi; Dwifi Aprilia Kharisma (LPPM of NAROTAMA UNIVERSITY, 2020)
The road is one of the most important infrastructures. The community needs it because the road functions to connect the source of production. Asphalt is an aggregate binding material in road pavement construction, which plays an important role in determining road pavement performance. Road Pavement, in general, uses materials that are still fairly common. This study uses a fine aggregate of crushed concrete specimens. The method used is an experiment on the addition of concrete test specimens with percentages of 10%, 20%, 30%, 40%, and 50%. Marshall method which is the basis for calculating the stability value and flow. the results of 5 Marshall test samples of asphalt concrete mix utilizing concrete waste obtained the characteristics of the average value of the study that all had met Highways' requirements at a VMA value of 18.22%, a value of 4.22 VIM.%, VFB value 75.04%, STABILITY value 4806 kg, FLOW value 3.24 mm, and Marshall Quotient (MQ) value 14958.1 kg / mm.